lo g 2 ( α 1 2 + β 1 2 + γ 1 2 + δ 1 2 )
Given that α , β , γ and δ are the roots of the equation x 4 + 4 x + 4 = 0 . Find the value of the expression above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Exactly !!
Log in to reply
Well i used newton sum...pretty long it was...Nice soln .
Its level 5!
exactly, same way. one thing is that if s 1 = s 2 = . . . = s n = 0 , p 1 = p 2 = p 3 = . . . = p n = 0 . so we see that both s 1 = s 2 = 0 , so p 1 = p 2 = 0 and p 3 = 3 s 3 = − 1 2 . doesn't take>1 minute to solve in head.
Exactly Same Way.
Sir , how did you get the general formula of ( α 1 2 + β 1 2 + γ 1 2 + δ 1 2 ) ?? Can we have a general formula for ( α n + β n + γ n + δ n ) , where n is any positive integer ???
Log in to reply
For α n + β n + γ n + δ n in general, we can use Newton's sums method or Newton's identities. Read this wiki .
o man!! i did same but forget writing +4 so get 64*12.............................
Problem Loading...
Note Loading...
Set Loading...
x 4 + 4 x + 4 ⇒ x 4 x 1 2 ⇒ α 1 2 + β 1 2 + γ 1 2 + δ 1 2 = 0 = − 4 ( x + 1 ) = − 4 3 ( x + 1 ) 3 = − 6 4 ( x 3 + 3 x 2 + 3 x + 1 ) = − 6 4 ( α 3 + β 3 + γ 3 + δ 3 + 3 ( α 2 + β 2 + γ 2 + δ 2 ) + 3 ( α + β + γ + δ ) + 4 )
By Vieta's formulas, we have:
α + β + γ + δ α 2 + β 2 + γ 2 + δ 2 α 3 + β 3 + γ 3 + δ 3 = 0 = ( α + β + γ + δ ) 2 − 2 ( α β + α γ + α δ + β γ + β δ + γ δ ) = 0 2 − 2 ( 0 ) = 0 = ( α + β + γ + δ ) ( α 2 + β 2 + γ 2 + δ 2 ) − ( α β + α γ + α δ + β γ + β δ + γ δ ) ( α + β + γ + δ ) + 3 ( α β γ + α β δ + α γ δ + β γ δ ) = ( 0 ) ( 0 ) − ( 0 ) ( 0 ) + 3 ( − 4 ) = − 1 2
Therefore,
α 1 2 + β 1 2 + γ 1 2 + δ 1 2 = − 6 4 ( α 3 + β 3 + γ 3 + δ 3 + 3 ( α 2 + β 2 + γ 2 + δ 2 ) + 3 ( α + β + γ + δ ) + 4 ) = − 6 4 ( − 1 2 + 3 ( 0 ) + 3 ( 0 ) + 4 ) = − 6 4 ( − 8 ) = 2 9
⇒ lo g 2 ( α 1 2 + β 1 2 + γ 1 2 + δ 1 2 ) = 9